The concept of sustainable regional development – institutional aspects, policies and prospects - Radislav Jovovic; Mimo Draskovic; Milica Delibasic; Miroslav Jovovic (Journal of International Studies)
Growing market globalization, increasing global competition, more complex products results in application of new technologies, methods and business processes – due to the abovementioned tendencies novel supply chain strategies (Lean, Agile and Leagile Supply Chains) are established. In this study these supply chain concepts are being described and compared. Virtual enterprise is a temporary alliance of enterprises that come together to share their skills, core competencies, costs and resources in order to better respond to rapidly changing market environment and dynamic customer demands. Economic and social benefits and effects of virtual enterprises for customers and production companies and service providers are also described. Optimization software has been developed for optimal formation of virtual enterprise networks and is also introduced in this study. The aim of this software application is to define virtual enterprise as the optimal combination of supply chain members.